1996
DOI: 10.1107/s0021889895007126
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Compton Scattering and Measurements of Momentum Distribution of Magnetic Electrons

Abstract: Recent progress in the field of magnetic Compton scattering is reviewed and new momentum-space information about electronic states in magnetic materials is emphasized. Theoretical derivation of the magnetic Compton scattering cross section is made within the framework of the nonrelativistic Hamiltonian of electrons in the electromagnetic field. Discussion on the orbital-spin contribution to the magnetic Compton scattering is also included as a Compton limit. The feasibility of the magnetic Compton scattering e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 47 publications
(62 reference statements)
0
69
0
Order By: Relevance
“…It is well known that MCP measurement observes only the spin contribution and the anisotropy of the MCP gives the anisotropy of spin projected momentum density. [12][13][14][15] Recently we have made the observation of anisotropy in magnetic Compton profiles of Co/Pd multilayers, 16,17 and succeeded to decompose symmetry of the Co 3d electron into the each magnetic quantum number, ͉m͉ = 0, 1, and 2. Then it has been found that both the ͉m͉ = 1 and 2 states of Co 3d electron contribute to the PMA.…”
Section: ͑3͒mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that MCP measurement observes only the spin contribution and the anisotropy of the MCP gives the anisotropy of spin projected momentum density. [12][13][14][15] Recently we have made the observation of anisotropy in magnetic Compton profiles of Co/Pd multilayers, 16,17 and succeeded to decompose symmetry of the Co 3d electron into the each magnetic quantum number, ͉m͉ = 0, 1, and 2. Then it has been found that both the ͉m͉ = 1 and 2 states of Co 3d electron contribute to the PMA.…”
Section: ͑3͒mentioning
confidence: 99%
“…[12][13][14] If we can understand the system as compose of independent particles described by single wave function, i ͑r͒ ͑ = majority spin or minority spin͒, within the limit of the impulse approximation, we can write for the momentum density by summing over all occupied single electron states of the system; 12…”
Section: Perpendicular Magnetic Anisotropy In Co/pt Multilayers Studimentioning
confidence: 99%
“…In x3, recent progress in highresolution Compton scattering spectroscopy is presented in order to demonstrate its potential. Recent magnetic Compton scattering experiments are not presented in this paper; instead the reader is referred to Sakai (1996) for details of recent magnetic Compton scattering experiments using a multi-element solid-state detector.…”
Section: Introductionmentioning
confidence: 99%
“…However, these photon sources are not optimal for high-resolution and magnetic Compton scattering experiments. Recent advents of highintensity, high-energy and well polarized synchrotron radiation sources offer new opportunities for developing Compton scattering as a tool for investigating Fermiologyrelated issues, electron±electron correlation effects and ferromagnetism in a wide class of materials Sakurai et al, 1992;Sakai, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation